2014
DOI: 10.1111/gtc.12135
|View full text |Cite
|
Sign up to set email alerts
|

The scaffold protein JLP plays a key role in regulating ultraviolet B‐induced apoptosis in mice

Abstract: The ultraviolet B (UVB) component of sunlight can cause severe damage to skin cells and even induce skin cancer. Growing evidence indicates that the UVB-induced signaling network is complex and involves diverse cellular processes. In this study, we investigated the role of c-Jun NH 2 -terminal kinase-associated leucine zipper protein (JLP), a scaffold protein for mitogen-activated protein kinase (MAPK) signaling cascades, in UVB-induced apoptosis. We found that UVB-induced skin epidermal apoptosis was prevente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…After treatments, the tissues were transferred to Tissue-Tek optimal cutting temperature (O.C.T, Sakura Finetek, Tokyo, Japan) compound to snap freeze for immunohistology. IHC was done as previously described [ 32 , 34 ]. Briefly, 10 µm tissue sections were air-dried on the slide glasses (Matsunami Glass, Osaka, Japan) for 40 min at RT, then washed with tris-buffered saline with 0.1% Tween20 (1× TBST) for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…After treatments, the tissues were transferred to Tissue-Tek optimal cutting temperature (O.C.T, Sakura Finetek, Tokyo, Japan) compound to snap freeze for immunohistology. IHC was done as previously described [ 32 , 34 ]. Briefly, 10 µm tissue sections were air-dried on the slide glasses (Matsunami Glass, Osaka, Japan) for 40 min at RT, then washed with tris-buffered saline with 0.1% Tween20 (1× TBST) for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Mice were then sacrificed at 6, 24, or 48 hr after bacterial administration. Frozen sections of reproductive tissues (cervix, uterus, placenta, fetal membrane, and pups) were subjected to microscopic analysis for the CFSE signal as described previously [ 60 ]. Briefly, the collected tissues were fixed in 4% PFA overnight at 4°C, then incubated in 30% sucrose for additional 24 hr at 4°C for cryoprotection.…”
Section: Methodsmentioning
confidence: 99%
“…The c‐Jun N‐terminal kinase (JNK)‐associated leucine zipper protein (JLP), also known as SPAG9 or JIP4, was first identified as a scaffold protein of the JNK and p38 MAPK signaling pathways (Kelkar et al, 2005; Lee et al, 2002). JLP‐JNK/p38 signaling plays a role in myogenesis (Takaesu et al, 2006), neurite outgrowth (Xu et al, 2010), and cell death (Boldbaatar et al, 2020; Enkhtuya et al, 2014; Li et al, 2018). Apart from scaffolding functions in MAPK pathways, JLP is considered to be involved in a variety of cellular processes, including cytokinesis and lysosome positioning (Kumar et al, 2022; Montagnac et al, 2009; Suzuki et al, 2020; Tuvshintugs et al, 2014; Willett et al, 2017), through its interacting proteins, like kinesin‐1 and cytoplasmic dynein 1 (hereafter, referred to as dynein).…”
Section: Introductionmentioning
confidence: 99%
“…JLP and its paralog JNK/stress‐activated protein kinase‐associated protein 1 (JSAP1) (Ito et al, 1999), also known as JIP3 (Kelkar et al, 2000), share similar domain structures, including JNK/p38 MAPK‐binding domain (MBD) and kinesin‐1 heavy chain (KHC)‐binding domains (KBD) (Ito et al, 2000; Sun et al, 2011), suggesting their functional redundancy. Additionally, gene knockout studies in mice have reported that JLP and JSAP1 have overlapping, as well as distinct functions: Jlp knockout mice are viable, grow normally, and exhibit male subfertility (Enkhtuya et al, 2014; Iwanaga et al, 2008), but Jsap1 knockout mice die just after birth due to respiratory failure (Ha et al, 2005; Kelkar et al, 2003). In contrast, studies with conditional knockout mice have revealed that although both Jlp and Jsap1 are involved in postnatal brain development (Sato, Ishikawa, Mochizuki, et al, 2015) and Purkinje cell survival (Sato, Ishikawa, Yoshihara, et al, 2015) in mice, their roles are redundant.…”
Section: Introductionmentioning
confidence: 99%